Estudo de caso das manifestações patológicas nas eclusas de Tucuruí: possíveis causas e tratamento - MAGALHÃES, Adonides da Silva (2018)
The Tucuruí locks are a work site characterized by a large volume of concrete (mass concrete). Although there is a strong control during the mixing of the concrete, the concrete execution and the cure phase, some pathological manifestations can appear in the structure. This is due to the environmental conditions in which the mass concrete is usually exposed, such as surface insulation and wind. As a most common pathological manifestation in concrete mass is the appearance of cracks due to the lack of evaporation control of the water, giving rise to shrinkage during drying. In this case study and the manifestation of cracking was also noted the emergence of air voids on the surface of concrete and concrete nests. Thus, this study aims to identify possible causes of the appearance of cracks and voids on the surface, as present the repair procedures used to treat them. In areas with the incidence of dry cracks (regions without the presence of moisture it was applied a structural adhesive based on an epoxy resin) and for the treatment of wet cracks (regions with the presence of moisture it was applied a injection polyurethane resin). In regions with a predominance of air voids in the concrete mass and nests, it was voids with mortar containing a silica fume. These materials and methods had a satisfactory performance in the treatment of theses problems. Thus, with an appropriate repair procedure and a correct execution it is possible to correct damage to the structures for increasing their durability.